REVIEW OF LITERATURE Comprehensive Physical and Systemic Examination in Neurological Disorders: Systemic examination in neurological disorders (Bombay Hospital Journal, 2026)
Introduction: A comprehensive general physical and systemic examination is fundamental in evaluating patients withneurological disorders. It helps not only in localizing neurological dysfunction but also in identifying systemic conditions, suchas diabetes, hypertension, and infections, that may contribute to or mimic neurological symptoms. A thorough examinationis crucial for accurate diagnosis and effective management. Key components of the physical examination: This includesan assessment of the patient’s general appearance, vital signs, head and neck, cardiovascular, respiratory, musculoskeletal,gastrointestinal and dermatological systems. Each of these aspects can reveal significant clinical findings, ranging from facialexpressions and posture indicative of specific neurological disorders to skin manifestations and cardiovascular irregularitiesthat provide clues for underlying conditions. The systemic examination’s depth depends on the patient’s history, yet a completeassessment is crucial for uncovering unexpected findings and ensuring accurate diagnosis and management of neurologicalconditions. Conclusion: By incorporating both targeted neurological and broader systemic assessments, this approachfacilitates the holistic evaluation of patients helping in optimizing treatment strategies for neurological disorders
Keywords: Amyotrophic lateral sclerosis, Mucopolysaccharidosis, Transient ischemic attack, Arteriovenous malformation